2012
DOI: 10.1002/glia.22418
|View full text |Cite
|
Sign up to set email alerts
|

Reduced connexin43 expression correlates with c‐Src activation, proliferation, and glucose uptake in reactive astrocytes after an excitotoxic insult

Abstract: In diverse brain pathologies, astrocytes become reactive and undergo profound phenotypic changes. Connexin43 (Cx43), the main gap junction channel-forming protein in astrocytes, is one of the proteins modified in reactive astrocytes. Downregulation of Cx43 in cultured astrocytes activates c-Src, promotes proliferation, and increases the rate of glucose uptake; however, so far there have been no studies examining whether this cascade of events takes place in reactive astrocytes. In this work, we analyzed this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 37 publications
2
23
0
1
Order By: Relevance
“…Finally, we used a conditional astrocytic Cx43 knockout (Cx43-KO) mouse as a glucose-deprivation model to confirm the importance of connexin-channel-based energy support on the OPC proliferation in both in vivo and co-culture systems. In these mice, glucose uptake in Cx43 lacking astrocytes is increased by compensatory upregulation of Glut1, Glut3 and type I/II hexokinase expression (Gangoso et al, 2012;Tabernero et al, 2006). As predicted, we observed that OPC proliferation was inhibited by Cx43 deletion in astrocytes without impacting on OPC hemichannel properties.…”
Section: Inhibition Of Hemichannel Activity Impacts Opc Proliferationsupporting
confidence: 85%
See 1 more Smart Citation
“…Finally, we used a conditional astrocytic Cx43 knockout (Cx43-KO) mouse as a glucose-deprivation model to confirm the importance of connexin-channel-based energy support on the OPC proliferation in both in vivo and co-culture systems. In these mice, glucose uptake in Cx43 lacking astrocytes is increased by compensatory upregulation of Glut1, Glut3 and type I/II hexokinase expression (Gangoso et al, 2012;Tabernero et al, 2006). As predicted, we observed that OPC proliferation was inhibited by Cx43 deletion in astrocytes without impacting on OPC hemichannel properties.…”
Section: Inhibition Of Hemichannel Activity Impacts Opc Proliferationsupporting
confidence: 85%
“…It has been reported that in astrocytes, Cx43 deletion increases glucose uptake by a compensatory upregulation of Glut transporters and/or glucose metabolism enzymes (Gangoso et al, 2012). To determine the influence of astroglial glucose over-consumption on the oligodendroglial lineage, we used the astrocyte Cx43 conditional knockout mouse (hGFAP Cre/+ :Cx43 fl/fl , Cx43-KO).…”
Section: Inhibition Of Hemichannel Activity Impacts Opc Proliferationmentioning
confidence: 99%
“…Cx43 is co-localized with b-catenin in cell membranes, sequestering this protein and negatively modulating b-catenin-dependent gene transcription in cardiac myocytes (Ai et al, 2000). Downregulation of Cx43 increases the expression of glucose transporter GLUT-3 through the activation of c-Src in cultured astrocytes (Gangoso et al, 2012). Cx43 has also been shown to modulate the expression of a number of genes (Iacobas et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…PNV contains excitotoxic neuropeptides [11] and PnTx1-3, a neurotoxin isolated from PNV, has been shown to increase the frequency of Ca 2+ oscillations in in vitro GH3 cells [44]. The significant further reduction of Cx43 expression, especially in the hippocampus (5 h post-PNV), could be a mechanism for avoiding cell damage [45], since PNV induces FOS induction (2 h post-PNV) in neurons [6] and the decrease of gap junctions (GJs) formation/communication in astrocytes could be controlled by neurons [42].…”
Section: Discussionmentioning
confidence: 99%